Synthesis and antimicrobial activity of s-substituted derivatives of 1,2,4-triazol-3-thiol - Karpun, Ye.; Polishchuk, N.; Карпун, Євген Олександрович; Поліщук, Наталія Миколаївна (My University, 2021)
The aim of the work. 1,2,4-triazole derivatives possess a wide range of pharmacological activity, so they are used for the development of drugs and active pharmaceutical ingredients.Due to the reactivity of 1,2,4-triazoles there are many options for their further structural modification on different reaction centers. Therefore, the aim of the work was toobtain new S-substituted derivatives of 1,2,4-triazole-3-thiols, study physicochemical parameters of the substances synthesized, evaluate the antimicrobial activity of new S-derivatives of the 4-R1-5-((3-(pyridin-4-yl)-1H-1,2,4-triazol-5-yl)thio)methyl)-4H-1,2,4-triazole-3-thiol series, and study some regularities of the “structure – biological activity” relationship for the synthesized compounds as well. Materials and methods. The subject of the study was new S-substituted 1,2,4-triazoles containing 2-oxopropan-1-yl and 2-aryl-2-oxoethan-1-yl substituents. The antimicrobial activity was studied by double serial dilutions on test cultures of Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), and Candida albicans (ATCC 885-653). The results of the biological screening showed that at a concentration of 125 g/mL, all synthesized substances showed activity (MIC – in the range of 31.25 – 62.5 μg/mL, MBCK – in the range of 62.5–125 μg/mL) against strains of Esche-richia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans. Variation of substituents on the sulfur atom did not lead to a significant change in antimicrobial and antifungal activities among derivatives of 4-R1-5-((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl) thio)methyl)-4H-1,2,4-triazole-3-thiols. Conclusions. Biological screening data indicate the prospects for the search for new antimicrobial substances among the abovementioned derivatives of 1,2,4-triazoles. The most active compounds were 1-((4-ethyl-5-((3-(pyridin-4-yl)-1H-1,2,4-triazol-5-yl)thio)methyl)-4H-1,2,4-triazol-3-yl)thio)propan-2-one and 1-(4-methoxyphenyl)-2-(4-ethyl-5-(((3-(pyridin-4-yl)-1H)-1,2,4-triazol-5-yl)thio)methyl)-4H-1,2,4-triazol-3-yl)thio)ethanone, which showed the most pronounced antimicrobial activity against the Pseudomonas aeruginosa strain (MIC – 31.25 μg/mL, MBcK – 62.5 μg/mL).
Keywords: 1,2,4-triazole; antibacterial activity; antifungal activity